New Management Guidelines for Mild Hypertension During Pregnancy. Issue 6 (November 2022) - Bernstein, Samantha L.
Abstract : After publication of an important randomized trial about the blood pressure threshold for medication treatment for mild hypertension in pregnancy, the American College of Obstetricians and Gynecologists and the Society for Maternal-Fetal Medicine issued a joint practice advisory on new guidelines for managing women with hypertensive disorders of pregnancy. Our maternity nursing expert, Dr. Bernstein, explains study findings and implications for clinical practice.